2005
DOI: 10.1111/j.1740-8261.2005.00037.x
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging Appearance of Suspected Ischemic Myelopathy in Dogs

Abstract: Ischemia and infarction of the spinal cord is a known cause of acute spinal injury in dogs. Currently, the diagnosis of spinal cord infarction in small animals is based on history, clinical signs, and the exclusion of other differentials with radiography and myelography. It is a diagnosis only confirmed through necropsy examination of the spinal cord. The aim of this paper is to describe the Magnetic resonance imaging (MRI) findings of the spinal cord of dogs with suspected spinal cord infarcts to utilize this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
77
2
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(82 citation statements)
references
References 17 publications
0
77
2
3
Order By: Relevance
“…[4][5][6]8 Because it is rare to definitively diagnose either condition prior to the death of the patient, both conditions are presumptively diagnosed on the basis of the presence of characteristic clinical findings in conjunction with established MRI criteria. [1][2][3][7][8][9] Although investigators of previous studies 1,2,5,8,10 have reported the characteristic clinical and diagnostic features of ischemic myelopathy and ANNPE separately, to our knowledge, no studies have been performed to compare the clinical signs and outcomes between ischemic myelopathy and ANNPE. Identification of any differences in the clinical findings and outcomes for these 2 conditions could be clinically relevant for attaining a presumptive antemortem diagnosis and developing both short-and long-term prognoses.…”
Section: Small Animals and Exoticmentioning
confidence: 88%
See 2 more Smart Citations
“…[4][5][6]8 Because it is rare to definitively diagnose either condition prior to the death of the patient, both conditions are presumptively diagnosed on the basis of the presence of characteristic clinical findings in conjunction with established MRI criteria. [1][2][3][7][8][9] Although investigators of previous studies 1,2,5,8,10 have reported the characteristic clinical and diagnostic features of ischemic myelopathy and ANNPE separately, to our knowledge, no studies have been performed to compare the clinical signs and outcomes between ischemic myelopathy and ANNPE. Identification of any differences in the clinical findings and outcomes for these 2 conditions could be clinically relevant for attaining a presumptive antemortem diagnosis and developing both short-and long-term prognoses.…”
Section: Small Animals and Exoticmentioning
confidence: 88%
“…A presumptive diagnosis of ischemic myelopathy or ANNPE was made on the basis of MRI criteria as described. 1,2,7 Briefly, criteria for ANNPE included a focal intramedullary hyperintensity overlying an intervertebral disk space on T2-weighted images, reduction in nucleus pulposus volume, mild narrowing of an intervertebral disk space, and the presence of extraneous material or a change in signal intensity relative to that for normal epidural fat within the extradural space. 2 Criteria for ischemic myelopathy included a focal intramedullary hyperintense lesion on T2-weighted images and the absence of the other criteria used to diagnose ANNPE.…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…based on past reports demonstrating the diagnostic utility of this methodology [1,5,7,10,12,14,15,17,18,20,24]. Twenty-five dogs survived and 1 dog was euthanized without post-mortem examination.…”
Section: Discussionmentioning
confidence: 99%
“…Antemortem diagnosis of FCE is based on history, clinical findings, and exclusion of other causes utilizing survey radiographs, cerebrospinal fluid (CSF) analysis, myelography, computed tomography, and magnetic resonance imaging (MRI) [3,8]. MRI is particularly helpful in supporting the antemortem diagnosis of ischemic myelopathy, because, in addition to excluding other causes of myelopathy, findings may reveal signal intensity changes compatible with spinal cord infarction [1,5,7,12,14,17,20,24]. The MRI features of definitive diagnosis of FCE have been described in a small number of cases in the veterinary literature [10,15,18,23].…”
mentioning
confidence: 99%